Questionnaire reliability and validity for aluminum potroom workers. - Kongerud, Johny; Vale, Jon Rasmus; Aalen, Odd O. (Scandinavian Journal of Work, Environment & Health, 1989)
As a part of a study on the respiratory symptoms of aluminum potroom workers, the reliability of a self-administered questionnaire and an interview questionnaire was studied with the use of 261 and 49 employees, respectively. The validity of the self-administered questionnaire (134 persons examined) and the interview questionnaire (90 persons examined) was assessed in a comparison of the statements with the case histories. The reliability of the self-administered questionnaire was fairly high, the kappa coefficient ranging from 0.58 to 0.83, while the reliability of the interview questionnaire varied from -0.03 to 0.45. The same pattern was present with regard to validity, as the self-administered questionnaire showed the highest mean sensitivity, specificity, and agreement in a comparison with the case histories. The self-administered questionnaire seemed to discriminate well between symptomatic and asymptomatic individuals, whereas supplemental information about symptoms, as obtained by a standardized interview questionnaire, appeared to be less valid.
Keywords: aluminum potroom; aluminum potroom worker; case history; evaluation; occupational history; questionnaire; reliability; respiratory symptom; validity; worker